"The Letter to the cossacks" - some lessons on pedagogy and political practice (PerCursos, 2024)
This article aims to address lessons of pedagogy and political practice in the work of the Marxist thinker Antonio Gramsci, especially regarding the reflections contained in the Prison Notebooks. The guiding thread of the text is the episode narrated by John Reed in his classic "Ten Days That Shook the World" about the Bolsheviks' ability to engage in dialogue with other political groups, even those considered potentially antagonistic, such as the cossacks. From there, the text explores the relation between intellectuals and the people, especially in Italy, and how Gramsci uses the concept of “rupture” among them to develop significant contributions to his political theory.
Keywords: Antonio Gramsci; pedagogy; philosophy